2017
DOI: 10.1101/183822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Raspberry Pi Powered Imaging for Plant Phenotyping

Abstract: ABSTRACT• Premise of the study: Image-based phenomics is a powerful approach to capture and quantify plant diversity. However, commercial platforms that make consistent image acquisition easy are often cost-prohibitive. To make high-throughput phenotyping methods more accessible, low-cost microcomputers and cameras can be used to acquire plant image data.• en masse using open-source image processing software such as PlantCV.• Conclusion: This protocol describes three low-cost platforms for image acquisition th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…IS such as red, green, and blue (RGB) sensors that take images within the wavelength range of 400-700 nm are termed visible IS, while IS that go beyond the visible wavelength are known as spectral IS (SIS) (Beisel et al, 2018;Bruning et al, 2020). In controlled conditions such as glasshouses or growth chambers, IS range from low-cost cameras to costly custom-made imaging setups (Tovar et al, 2018). Recently, Xia et al (2019) used hyperspectral and RGB to phenotype WL in rape plants and found promising results.…”
Section: Application Of Htrp Under Waterloggingmentioning
confidence: 99%
“…IS such as red, green, and blue (RGB) sensors that take images within the wavelength range of 400-700 nm are termed visible IS, while IS that go beyond the visible wavelength are known as spectral IS (SIS) (Beisel et al, 2018;Bruning et al, 2020). In controlled conditions such as glasshouses or growth chambers, IS range from low-cost cameras to costly custom-made imaging setups (Tovar et al, 2018). Recently, Xia et al (2019) used hyperspectral and RGB to phenotype WL in rape plants and found promising results.…”
Section: Application Of Htrp Under Waterloggingmentioning
confidence: 99%